2013
DOI: 10.1063/1.4804671
|View full text |Cite
|
Sign up to set email alerts
|

The role of the (111) texture on the exchange bias and interlayer coupling effects observed in sputtered NiFe/IrMn/Co trilayers

Abstract: Magnetic properties of sputtered NiFe/IrMn/Co trilayers grown on different seed layers (Cu or Ta) deposited on Si (100) substrates were investigated by magnetometry and ferromagnetic resonance measurements. Exchange bias effect and magnetic spring behavior have been studied by changing the IrMn thickness. As shown by X-ray diffraction, Ta and Cu seed layers provoke different degrees of (111) fcc-texture that directly affect the exchange bias and indirectly modify the exchange spring coupling behavior. Increasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…Moreover, indirect interlayer coupling between FM layers across AF metallic layer like RKKY and orange-peel interactions between FM layers separated by a non-magnetic layer vanishes at the AF spacer thickness of the order of few nanometers [24][25][26][27]. Therefore, the suggestion about the existence of magnetic coupling between the FM layers through the AF layer is quite rare [28,29].…”
Section: Introductionmentioning
confidence: 92%
“…Moreover, indirect interlayer coupling between FM layers across AF metallic layer like RKKY and orange-peel interactions between FM layers separated by a non-magnetic layer vanishes at the AF spacer thickness of the order of few nanometers [24][25][26][27]. Therefore, the suggestion about the existence of magnetic coupling between the FM layers through the AF layer is quite rare [28,29].…”
Section: Introductionmentioning
confidence: 92%
“…After that, when the sample is saturated in negative fields the alignment is P again [6,9]. In order to estimate some magnetic parameters from the curves, the derivatives of the descending and ascending branches of the loop were calculated [18][19][20] investigated NiFe/IrMn/Co trilayers grown on Ta or Cu seed layers and found that crystalline texture influences the trilayers' magnetic properties [22]. This way, as discussed above, the difference of the H C and H EB values for S Nb when compared to those for S Ta , obtained at 6 K, may be attributed to the degree of (200) preferred orientation of the IrMn layer in S Nb .…”
Section: Resultsmentioning
confidence: 99%
“…In previous work [20], it has been shown that the Cu (Ta) buffer layer induced a low (high) degree of [111] fiber-texture in the Si(100)/ Cu or Ta(10 nm)/Ni 80 Fe 20 (20 nm)/Ir 20 Mn 80 (4-15 nm)/Co(10 nm)/Ta or Cu(10 nm) deposited by oblique incidence in a confocal magnetron sputtering with the sample holder spinning at 0.5 Hz. The samples with high degree of [111] texture (with Ta buffer) presented a strong planar magnetic anisotropy, opposite to what happened to the samples with Cu.…”
Section: Introductionmentioning
confidence: 97%